2023
DOI: 10.1038/s44160-023-00341-3
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven C–O coupling of carboxylic acids and alkyl halides over a Ni single-atom catalyst

Abstract: The coupling of two sp 3 hybridized fragments remains a challenging protocol for organic synthesis. Although visible light-driven dual photoredox catalysis, a method that combines photoabsorbers and transition metals, has become a powerful tool to conduct such transformations, resource economical and scalability issues persist, due

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 76 publications
0
20
0
1
Order By: Relevance
“…245 The abundance of nitrogen in g-CN can offer lone pairs of electrons to form a strong bond with the empty or partially empty orbitals of metal atoms, which significantly stabilises the formed SACs. 231,[246][247][248][249][250][251][252][253][254] Furthermore, their thermal/chemical stability, moderate band gap, extended p conjugation to stabilize the metal centre via charge transfer, and periodicity of active sites make them ideal materials to fabricate SACs. [255][256][257] These SACs can be loaded at the defect sites on g-CN to obtain single-atom loaded g-CN through a low-cost, facile and eco-friendly topdown mechanochemical abrasion and solvent-free approach, coupled with mild thermal treatment.…”
Section: Band Gap Engineering Of G-cnmentioning
confidence: 99%
“…245 The abundance of nitrogen in g-CN can offer lone pairs of electrons to form a strong bond with the empty or partially empty orbitals of metal atoms, which significantly stabilises the formed SACs. 231,[246][247][248][249][250][251][252][253][254] Furthermore, their thermal/chemical stability, moderate band gap, extended p conjugation to stabilize the metal centre via charge transfer, and periodicity of active sites make them ideal materials to fabricate SACs. [255][256][257] These SACs can be loaded at the defect sites on g-CN to obtain single-atom loaded g-CN through a low-cost, facile and eco-friendly topdown mechanochemical abrasion and solvent-free approach, coupled with mild thermal treatment.…”
Section: Band Gap Engineering Of G-cnmentioning
confidence: 99%
“…[11] Very recently, Vilé and Tosoni developed a single-atom Nicatalyzed CÀ O coupling of carboxylic acids and alkyl halides under visible light. [12] Over time, cobalt as an earth-abundant transition metal, in its single-atom form, has exhibited great potential in the discovery of new reactions, including fluorination of acyl chlorides reported by Wang and Tang, [13] N-heterocycle and 1,2-diamine synthesis from nitroarene by Zhang, [14] and tunable synthesis of aziridine and oxyamination products from alkenes by our group. [15] CÀ C bond represents one of the most widespread chemical bonds in organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysis is a recently developed concept that is being widely investigated for several catalytically active metals on various supports for various reactions. It has been demonstrated that the support material plays a fundamental role in the catalytic activity of single-atom catalysts. , Unlike many other metals synthesized as single-atom catalysts, which can readily be synthesized, stabilized, and reveal a high efficiency, , Pd single atom (Pd SA ) requires overly cumbersome synthesis methods and suffers lower stabilization . Furthermore, the ligand–metal charge transfer , and the metal–metal interactions are well-established phenomena that must be investigated separately for each species in catalysis, which are also crucial to understanding the catalytic behavior of Pd.…”
Section: Introductionmentioning
confidence: 99%